2014
DOI: 10.3126/ijasbt.v2i4.11531
|View full text |Cite
|
Sign up to set email alerts
|

Study of Corrosion Inhibition Mechanism of Sputter-Deposited W-42Cr-5Ni and Cr-10Zr-10w Alloys by Sodium Nitrite as Green Inhibitor in 0.5 M NaCl and 1 M NaOH Solutions

Abstract: The effect of different concentrations of sodium nitrite as a green corrosion inhibitor on the corrosion inhibition mechanism of the sputterdeposited ternary W-42Cr-5Ni and Cr-10Zr-10W alloys was studied in 0.5 M NaCl and 1 M NaOH solutions open to air at 25ºC using corrosion tests. The use of the sodium nitrite enhanced the corrosion resistance properties of both the alloys in 0.5 M NaCl and 1 M NaOH solutions. It is found that the sodium nitrite is strongly adsorbed on the surface of the sputter-deposited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To solve such a problem of the preparation of Wbased alloys in a wide composition range was successfully solved using the sputter deposition technique since 1995 AD. The sputter-deposited binary amorphous or nano-crystalline tungsten alloying with metals; chromium [44][45][46][47], titanium , zirconium [29,53], molybdenum [54][55][56], niobium [57][58][59][60], and tantalum [61][62][63][64], nickel [65][66][67], and ternary W-Cr-Ni [68][69][70][71] and W-Cr-Zr [72][73][74][75][76][77][78][79] alloys were prepared in the wide composition range and they showed higher corrosion resistance than those of alloy-constituting metals in corrosive environments of HCl, NaCl, and NaOH solutions.…”
Section: Introductionmentioning
confidence: 99%
“…To solve such a problem of the preparation of Wbased alloys in a wide composition range was successfully solved using the sputter deposition technique since 1995 AD. The sputter-deposited binary amorphous or nano-crystalline tungsten alloying with metals; chromium [44][45][46][47], titanium , zirconium [29,53], molybdenum [54][55][56], niobium [57][58][59][60], and tantalum [61][62][63][64], nickel [65][66][67], and ternary W-Cr-Ni [68][69][70][71] and W-Cr-Zr [72][73][74][75][76][77][78][79] alloys were prepared in the wide composition range and they showed higher corrosion resistance than those of alloy-constituting metals in corrosive environments of HCl, NaCl, and NaOH solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Past researches had reported that some organic [20][21][22][23][24][25] and inorganic [26][27][28][29][30] compounds were used as eco-friendly corrosion inhibitors because they form complexes with metal ions on metal/alloy surface. Investigations of corrosion-inhibiting ability of inorganic radicals or ions, e.g., nitrites, molybdates, tungstates, polyphosphates are now being increasingly used as eco-friendly inhibitor due to their zero-toxic nature [10,[31][32][33][34][35][36]. It was reported that calcium nitrate acted as retarder against chloride-induced concrete structures like well-known corrosion inhibitor of calcium nitrite [37] because it is also cheaper, less harmful and more available [38].…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in replacing chromates with effective and non-hazardous alternatives eco-friendly green corrosion inhibitors. Nitrites, molybdate, tungstate are now being increasingly used as eco-friendly green inorganic corrosion inhibitors due to their low order of toxicity [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%